State of the Streaming Industry in the U.S. After Crisis in 2022 - Jeongsuk Joo (International Journal of Advanced Culture Technology(IJACT), 2025)
This paper keeps track of the state of the streaming industry in the U.S. after it hit its first major crisis in 2022 and provides insights into its development, as streaming services are the most important industry that shapes the present and the future of television and how we consume entertainment. The streaming industry, faced with the crisis of the drop in subscribers and huge losses in 2022, has undergone changes to cut costs and improve profit. Netflix has since returned to growth and maintains its market-leading position, but Disney and other media companies continue to struggle to see profit, raising the question whether all media companies can survive the transition to the streaming age. At the same time, while streaming services are now the primary form of television viewing, shifting user loyalty could imperil the long-term growth of streaming companies, pointing to the need to learn to strike a balance between pursuing profit and trying to maintain user loyalty.